National Economic Security and its Military Political Aspects - A. M. Kuzmenkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
In modern conditions, aggravation of problems of ensuring national security of Russia is observed. It is caused by influence of a complex of factors. Authors consider the situation developing in the sphere of ensuring economic and military security of the country. For the analysis both empirical materials and expert estimates, and objective statistical data from the Russian and international sources are used. Authors prove a conclusion about existence of close interrelation of military and economic security, impossibility and inexpediency of their separate consideration in the theoretical analysis that generates need of correction of institutional mechanisms of their providing. At the same time, the conclusion is drawn on priority of start in Russia of mechanisms of sustained economic growth: without solution of this task, ensuring national security in the military and economic sphere will be, according to authors, extremely difficult.